Desempenho em consciência fonológica, memória operacional, leitura e escrita na dislexia familial - Capellini, Simone Aparecida [UNESP] (2007)
Background: familial dyslexia. Aim: to characterize and compare the phonological awareness, working memory, reading and writing abilities of individuals whose family members are also affected. Method: in this study 10 familial nuclei of natural family relationship of individuals with dyslexia were analyzed. Families of natural individuals living in the west region of the state of São Paulo were selected. Inclusion criteria were: to be a native speaker of the Brazilian Portuguese language, to have 8 years of age or more, to present positive familial history for learning disabilities, That is, to present at least one relative with difficulties in learning. Exclusion criteria were: to present any neurological disorder genetically caused or not, in any of the family members, such as dystonia, extra pyramidal diseases, mental disorder, epilepsy, attention deficit and hyperactivity disorder (ADHA); psychiatric symptoms or conditions; or any other pertinent conditions that could cause errors in the diagnosis. As for the diagnosis of developmental dyslexia, information about the familial history of the adolescents and children was gathered with the parents, so that a detailed pedigree could be delineated. Neurological, psychological, speech-language, and school performance evaluations were made with the individuals and their families. Results: the results of this study suggest that the dyslexic individuals and their respective relatives, also with dyslexia, presented lower performances than the control group in terms of rapid automatic naming, reading, writing and phonological awareness. Conclusion: deficits in phonological awareness, working memory, reading and writing seem to have genetic susceptibility that possibly determine, when in interaction with the environment, the manifestation of dyslexia.